Acquisition, prospecting and development of mineral properties in Ghana - Morna, Bryne Ansin (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of Postgraduate Professional Diploma in Mining Engineering,